Syncope Prognosis Based on Emergency Department Diagnosis: A Prospective Cohort Study. (11th January 2018) - Toarta, Cristian; Mukarram, Muhammad; Arcot, Kirtana; Kim, Soo‐Min; Gaudet, Sarah; Sivilotti, Marco L. A.; Rowe, Brian H.; Thiruganasambandamoorthy, Venkatesh
Abstract: Objective: Relatively little is known about outcomes after disposition among syncope patients assigned various diagnostic categories during emergency department (ED) evaluation. We sought to measure the outcomes among these groups within 30 days of the initial ED visit. Methods: We prospectively enrolled adult syncope patients at six EDs and excluded patients with presyncope, persistent mental status changes, intoxication, seizure, and major trauma. Patient characteristics, ED management, diagnostic impression (presumed vasovagal, orthostatic, cardiac, or other/unknown) at the end of the ED visit, and physicians' confidence in assigning the etiology were collected. Serious outcomes at 30 days included death, arrhythmia, myocardial infarction, structural heart disease, pulmonary embolism, and hemorrhage. Results: A total of 5, 010 patients (mean ± SD age = 53.4 ± 23.0 years; 54.8% females) were enrolled; 3.5% suffered serious outcomes—deaths (0.3%), arrhythmias (1.8%), nonarrhythmic cardiac (0.5%), and noncardiac (0.9%) including pulmonary embolism (0.2%). The cause of syncope was presumed as vasovagal among 53.3% and cardiac in 5.4% of patients. The proportion of patients with ED investigations (p < 0.001) and short‐term serious outcomes (p < 0.01) increased in each diagnostic category in the following order: presumed vasovagal, orthostatic hypotension, other/unknown cause, and cardiac. No deaths occurred in patients with presumed vasovagal syncope. A higher proportion of all serious outcomes occurred among patients suspected of cardiac syncope in the ED (p < 0.01). Confidence was highest among physicians for a presumed vasovagal syncope diagnosis and lowest when the cause was other/unknown. Conclusion: Short‐term serious outcomes strongly correlated with the etiology assigned in the ED visit. The importance of the physician's clinical judgment should be further studied to determine if it should become incorporated in risk‐stratification tools for prognostication and safe management of ED syncope patients.